The Effect Of Snakebite On Hemodynamic Disorders Of The Heart In Adults And Pregnant Women - R. Mohamad Javier; Tiara Josephine Gracienta; Diana Khoirun Nida; Vania Putri Salsabilla; Safira Dita Arviana; Maren Irgiwi Fadlilah (Syntax Corporation Indonesia, 2023)
A snake bite is a natural defense response from a snake and can be an emergency medical situation. Snakes have a venom consisting of various proteins that can affect the functioning of the human body. The venom structure in snake venom varies between different species of snakes. Knowing the effect of snakebite on hemodynamic disorders of the heart in adults and pregnant women. This study is a Systematic Review that applies the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) method, which is a systematic approach that follows appropriate research steps and protocols. The result of this study is the association of Snakebite with Hemodynamic Disorders of the Heart in Adult Patients and Pregnant Women